Evaluasi Program Praktik Industri (PI) Di Program Studi Pendidikan Teknik Informatika Dan Komputer Fakultas Teknik Universitas Negeri Makassar - Musdalifah Djamaluddin (LLDikti Wilayah IX Sulawesi dan Gorontalo, 2019)
The purpose of this evaluation research is to determine the achievement of the implementation of Industrial Practices in the Informatics and Computer Engineering Education Study Program, Faculty of Engineering, Makassar State University in 2016 in terms of Context Evaluation, Input Evaluation, Process Evaluation, Product Evaluation. This research is an evaluation research with the object of research of the implementation of Industrial Practices conducted in the Study Program of PTIK FT UNM. Sources of data in this study were supervisors of Industrial Practice students, Industrial Practice advisers in the field and students in the PTIK FT UNM Study Program who carried out Industrial Practices in 2016. Students who were respondents were sampled with simple random sampling technique, the evaluation model used was evaluation models (Context, Input, Process, Product) with quantitative evaluation methods. Data collection was taken through questionnaires, observations, interviews and documentation. Data analysis using quantitative descriptive and presented in the form of tables and histograms. The results of the study stated that: (1) The suitability of the implementation of Industrial Practices based on the Industrial Practices manual in the Study Program of PTIK FT UNM in 2016 in terms of Context Evaluation was included in the category according to the average value of 80. (2) The suitability of the implementation of Industrial Practices based on the book Industrial Practice guidelines in the Study Program of PTIK FT UNM in 2016 in terms of Input Evaluation included in the category in accordance with an average value of 82.7. (3) The appropriateness of the implementation of Industrial Practices based on the manual in the Study Program of PTIK FT UNM in 2016 in terms of Process Evaluation is included in the category according to the average value of 81.25. (4) The appropriateness of the implementation of Industrial Practices based on the guidebook in the Study Program of PTIK FT UNM in 2016 in terms of Product Evaluation is included in the category very in accordance with the average value of 90.5.